Prevention of iodine deficiency disorders in pregnant and lactating women. Current recommendations for the use of iodide potassium - E A Troshina (IP Berlin A.V., 2014)
A critical consequence of chronic iodine deficiency during fetal development and early childhood is a violation of intellectual development. The need and the order of iodine prophylaxis in pregnant and lactating women identified the World Health Organization (WHO) and the International Council for Control of iodine deficiency disorders (IDD - ICCIDD). Pregnant and lactating women are referred to the absolute risk of developing IDD. WHO and ICCIDD recommend prescribe potassium iodide for women during pregnancy and breast-feeding, living in areas of iodine deficiency. Order № 50 of the Ministry of Health and Social Development of the Russian Federation from 2007 identified essential drugs for women during pregnancy and the postpartum period, which also made the preparations of potassium iodide. Russia's recommendations on the level of iodine intake by pregnant and nursing women conform to WHO recommendations. Federal standards of care for pregnant women include prescription drugs, potassium iodide.